Efficient and practical organocatalytic system for the synthesis of cyclic carbonates from carbon dioxide and epoxides: 3-hydroxypyridine/tetra-n-butylammonium iodide. Issue 8 (23rd February 2017) - Wang, Xiangyong; Wang, Lin; Zhao, Yingying; Kodama, Koichi; Hirose, Takuji
Abstract: An efficient and practical organocatalytic system comprising 3-hydroxypyridine and tetra- n -butylammonium iodide was developed for the synthesis of cyclic carbonates from carbon dioxide and epoxides under mild conditions (1 atm CO2, 25–60 °C) without organic solvent. By comparing with related hydroxypyridine derivatives, the effects of the hydroxyl group, the acidity and the steric factor, were discussed. Study on the mixtures of CO2 and N2 in various ratios indicated that the yield depends on CO2 content, due to the solubility of CO2 in the reaction mixture. The system was also shown not to be deteorated by the presence of H2 O, air or O2 . Graphical abstract: